A semi-analytical model of the train-floating slab track–tunnel–soil system considering the non-linear wheel/rail contact. (September 2018) - Zhang, Xiaohui; Zhou, Shunhua; Di, Honggui; He, Chao
This paper presents a three-dimensional model for the calculation of train-induced vibration of a floating slab track in an underground tunnel based on the integration of a semi-analytical approach and a dynamic substructure method. The methodology for the train-floating slab track–tunnel–soil coupled model is described and validated by comparing the vibration response of the system with that of the Pipe-in-Pipe model. The innovations of the proposed model include the following: (1) it considers all components of the metro train-induced vibration problem including the train, the floating slab track, the tunnel, the soil and the interactions of the subsystems; and (2) it operates in the time domain and thus is capable of modelling the highly non-linear loading behaviours (i.e. the wheel/rail contact relationship). A hypothetical example is presented to illustrate the vibration isolation effect of the floating slab track using the developed model, and the following conclusions can be drawn. Excellent vibration isolation performance is observed for the floating slab track system, especially for vibrations at a high frequency (above 12.5 Hz), whereas the vibration is amplified near the natural frequency of the floating slab (i.e. 8 Hz in this study) because of the resonance effect. The amplitudes of the soil stresses are reduced due to the floating slab track system, especially for the high-frequency soil stresses.